Inseminação artificial em tempo fixo e diagnóstico precoce de gestação em vacas leiteiras mestiças - Barbosa, Cláudio França (2009)
This study aimed to evaluate the reproductive performance of 94 Bos taurus x Bos indicus crossbred dairy cows for one year, undergoing a program of assisted reproduction. One protocol for timed artificial insemination (TAI) was performed through intravaginal progesterone inserts, injections of prostaglandin F2 (PGF2) and estradiol cypionate (EC). Ovulation s detections were performed by ultrasonography between the seventh and fourteenth day and executions of pregnancy diagnosis (PD) to the twenty eighth day after the inseminations. It was honored a voluntary waiting period (VWP) of 45 days after calving, before the first service. There was no influence of the body condition score (BCS) and corpus luteum (CL) presence before the start of the protocol, neither of reuse of the intravaginal insert and controlled mount (CM) or artificial insemination (AI) on rates of ovulation (OR), conception (CR) and conception of ovulated cows (COCR). Significant effect (P<0.05) was detected in the number of days in milk (DIM) and time of the year on the CR and COCR.